Analysis of radioactive waste generated during the cyclotron production of 99mTc. (25th February 2019) - Stothers, L A; Hou, X; Vuckovic, M; Buckley, K; Bénard, F; Schaffer, P; Celler, A
Abstract: Past and prospective shortages of medical radioisotopes have driven recent developments in the direct production of 99m Tc via the 100 Mo(p, 2n) 99m Tc reaction. The cyclotron-based production method has been shown to successfully produce 99m Tc, however trace impurities present in the enriched molybdenum target can also lead to the unintended creation of other radioisotopes which constitute waste. The isotopic composition of the waste has to be investigated in order to determine how it can be handled, transported and safely stored. In this article, we report which waste radioisotopes are created alongside 99m Tc during target irradiation. Results are based on the gamma spectroscopy of waste produced. Significant complexities in the emission spectra made automated identification of radioisotopes inaccurate; complexities were resolved using a manual radioisotope identification procedure. The impact of target composition, integrated beam current and duration of target irradiation on the waste produced was studied. Results indicate that an average of 0.059  ±  0.003 GBq of waste is generated per 1 GBq of 99m Tc produced. Two-thirds of the total waste activity produced was attributed to 99 Mo ( T 1/2   =  66 h) alone, while a total of fifty radioisotopes were found in the waste. Long-lived isotopes ( T 1/2   >  2 months) constituted only 1% of the total waste activity at end of beam (EOB). In conclusion, it was determined that the waste generated during cyclotron-based 99m Tc production was acceptably low for routine clinical production.